PREPARATION OF INTRAMUSCULAR DRUGS IN PEDIATRICS: NURSING TEAM - Rafaela de Oliveira Mota; Eva Anny Wélly de Souza Brito; Thais Lima Vieira de Souza; Laryssa Miranda Vidal Cavalcante Farias; Érica Oliveira Matias; Francisca Elisângela Teixeira Lima (Universidade Federal do Paraná, 2016)
The objective of this study was to analyze work by a nursing team regarding the environmental organization, preparation and dilution of drugs administered intramuscularly in a pediatric setting. This was an observational and quantitative study developed through 327 observations of the preparation of intramuscular medication from December 2014 to May 2015 in a pediatric hospital in Fortaleza, in the state of Ceará. Observations employed a two-stage checklist: organization of the environment with four actions; preparation and dilution of medications with 12 actions. For organization of the environment, performance regarding the action of organizing the bench with a count of 231 (70.6%) was satisfactory. The stage of medication preparation and dilution achieved satisfactory performance in six actions: separation of cotton balls soaked with alcohol from dry ones with 252 (77%); selection of syringe compatible with the volume to be administered with 264 (80.7%); proper selection of the needle for aspiration with 233 (71.2%); needle for administration with 320 (97.8%); change of needle after preparation with 266 (81.3%); reconstitution of medication in distilled water with 327 (100%). This allowed for the identification of weaknesses, such as observing the sell-by date of medications and identifying the medications prepared, actions that interfere with the safe administration of medications in pediatrics.